1995
DOI: 10.1007/bf00315789
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a mutant defective in a putative phosphoinositide-specific phospholipase C of Schizosaccharomyces pombe is restored by low concentrations of phosphate and inositol

Abstract: A mutant (plc1-1) of Schizosaccharomyces pombe unable to grow on a minimal medium containing high amounts of phosphate was selected. On yeast-extract agar its growth is temperature sensitive. Tests in liquid synthetic medium show that growth of the mutant is partially restored by lowering the phosphate and inositol concentrations in the growth medium. The growth defect is fully suppressed by a plasmid encoding a putative protein having the structural features of phosphoinositide-specific phospholipases C (PI-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…PLC genes have been identiWed in diverse eukaryotic organisms other than mammals, including the slime mold (Dictyostelium discoideum) (Drayer and Van Haastert, 1992) and yeast (Bennett et al, 1998;Fankhauser et al, 1995;Yoko-o et al, 1993). In addition, there is growing evidence to implicate phosphoinositides in the signal transduction pathway of Wlamentous fungi (Gadd, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…PLC genes have been identiWed in diverse eukaryotic organisms other than mammals, including the slime mold (Dictyostelium discoideum) (Drayer and Van Haastert, 1992) and yeast (Bennett et al, 1998;Fankhauser et al, 1995;Yoko-o et al, 1993). In addition, there is growing evidence to implicate phosphoinositides in the signal transduction pathway of Wlamentous fungi (Gadd, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that the percentage of phosphatidylinositol present in phospholipids strongly depends on the inositol concentration in the growth medium (Fernandez et al 1986). Genes encoding phospholipase C and phosphatidylinositol-speci®c PI 3-kinase have been identi®ed (Andoh et al 1995;Fankhauser et al 1995a;Takegawa et al 1995). Phospholipase C interacts with the 14-3-3 protein encoded by rad24 and is involved in the control of resistance to UV irradiation (Andoh et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…The deduced amino acid sequence of the S. pombe TPK gene (tnr3) (17) was used to conduct a text-based search of the mouse EST database at the National Center for Biotechnology Information. The sequence information of the obtained mouse clone AA981202 allowed the synthesis of three specific primers, F1 (5Ј-TGACCAAATCATGGC-CTCTGTG), R1 (5Ј-TTCATGCTGAGCAACGAACCAG), and R2 (5Ј-TTAGCTCTTGATGGCCATGGT).…”
Section: Methodsmentioning
confidence: 99%
“…4). The amino acid sequence of mTPK1 showed 39% identity with the carboxyl-terminal half of tnr3, which appears as a fusion protein (569 amino acids) with unknown function at the amino-terminal half (17). The mTPK1 protein was also similar to THI80 and pTPK1 over their full lengths (31% of amino acid identity).…”
Section: Fig 2 Functional Complementation Of the Yeast Thi80 Mutantmentioning
confidence: 96%
See 1 more Smart Citation